Pre-hormonal therapy combined with buccal mucosal graft for glans reconstruction in complete penile amputation: A case report and review of literature - Joko Pitoyo; Albert Ciam (Urology Case Reports)
Penile amputation following circumcision is a rare but serious complication. Reconstructing the glans poses a complex surgical challenge, and several techniques have been proposed to address this issue. We present the case of a 10-year-old boy who experienced complete glans amputation 14 hours after circumcision. The initial remaining penile length was measured at 2 cm. We performed stump repair and planned for staged surgery. Buccal mucosal grafting for neo-glans reconstruction, combined with testosterone pre-hormonal therapy, proved to be a simple procedure with satisfactory results. This case provides valuable insights into the management of similar cases in the future.